Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nano10071253
|View full text |Cite
|
Sign up to set email alerts
|

Surface Degradation Mechanism on CH3NH3PbBr3 Hybrid Perovskite Single Crystal by a Grazing E-Beam Irradiation

Abstract: To start a step such as some realization of minimized and integrated devices, it requires simply understanding the surface status of hybrid perovskite on the e-beam irradiation because many commercial semiconductor devices are performed with a surface patterning process using e-beam or etching gas. The surface status of CH3NH3PbBr3 (MAPbBr3) single crystal was studied after a grazing e-beam irradiation in an ultra-high vacuum. The prepared hybrid perovskite single crystal was irradiated by the 3 degree-grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…C, N, and Br were decomposed as volatile species, then escape the sample surface similar to simple outgassing. Interestingly, a similar degradation process was also observed under E-Beam Irradiation [99].…”
Section: Light Exposure On Mapbbr 3 Single Crystalsupporting
confidence: 71%
“…C, N, and Br were decomposed as volatile species, then escape the sample surface similar to simple outgassing. Interestingly, a similar degradation process was also observed under E-Beam Irradiation [99].…”
Section: Light Exposure On Mapbbr 3 Single Crystalsupporting
confidence: 71%
“…Br 2 formation upon MAPbBr 3 and FAPbBr 3 illumination is expected from the known photo-decomposition (photolysis) of PbBr 2 to Pb 0 and Br 2 , 27,28 similar to PbI 2 decomposition, 55 and from analogy with FAPbI 3 or MAPbI 3 perovskites, which were shown to release I 2 upon illumination. 12,82 Also, Pb 0 and consequent Br 2 loss was identified by other groups after e-beam 83 or X-ray. 84 It is reasonable to think that, with time, Pb 0 will react with the slightly acidic MA + /FA + cations forming H 2 , methylamine/formamidine and PbBr 2 .…”
Section: Surface and Bulk Stability: The Role Of The A Cationmentioning
confidence: 78%
“…29−31 Additionally, damage, degradation, and desorption of the organic section and Br 2 were observed. 29 (2) Morphological transformations from NC into microscale solids and the aging instability of the NCs were also previously found. 32 The authors used surface engineering to prevent the undesired growth and morphological changes in the solution.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…Energy-dispersive X-ray spectroscopy (EDS) analysis showed that the Br/Pb ratio was not in good agreement with the PbBr 3 stoichiometry (see Figure S1 in the Supporting Information). Two facts may explain the discrepancy with the theoretical ratio: (1) previous studies revealed that the halide perovskite decomposes during the TEM measurements. Additionally, damage, degradation, and desorption of the organic section and Br 2 were observed . (2) Morphological transformations from NC into microscale solids and the aging instability of the NCs were also previously found .…”
Section: Resultsmentioning
confidence: 91%